Analisis Pengendalian Internal Atas Transaksi Pengeluaran Kas Pada Dinas Kesehatan Provinsi Sumatera Barat - Febryandhie Ananda; Mustika Winda; Riani Sukma Wijaya (JURNAL PUNDI, 2022)
This research aims toto find out how to implement the internal control system for cash disbursements at the West Sumatra Provincial Health Office and to find out what obstacles arise in the implementation of the cash disbursement internal control system at the West Sumatra Provincial Health Office. This type of research is qualitative research, the data comes from several things, namely in the form of words and actions. The rest is additional data such as documents and others. To complete the research data, two data sources are needed, namely primary data sources and secondary data sources. The analytical method used in this research is descriptive analysis method, which is a method that aims to make a systematic, factual and accrual description of the facts, by comparing the theoretically studied cash disbursement procedure systems.The results of the observations presented by the author use closed questions through interviews with several trusted sources who work at the West Sumatra Health Office. The results of the study found that the cash disbursement procedure carried out by the West Sumatra Provincial Health Office was smooth and theoretical but not all procedures were the same because in a company there were different parties and different functions together. Procedures related to the cash disbursement system at the West Sumatra provincial health office have inconsistent procedures, namely the limited time in processing submitted documents, usually only 3 days, but some are neat in 5 days because the data checklist is not reviewed by PPKSKPD and Expenditures. The treasurer verifies the SPM document to be submitted to BPKAD.